Cutaneous manifestations of Mycobacterium gordonae infection described for the first time in Italy: a case report - Foti, Caterina (BioMed Central, 2009)
INTRODUCTION: Mycobacterium gordonae is one of the least pathogenic of the mycobacteria. This pathogen may produce caseating or non-caseating granulomas, and skin lesions showing acute or chronic inflammation with scattered histiocytes and giant cells have been seen. The mortality rate is less than 0.1%. Mycobacterium gordonae may be a marker of severe immunosuppression in patients infected with human immunodeficiency virus. CASE PRESENTATION: We report a case of Mycobacterium gordonae infection in an 86-year-old woman and discuss the problems inherent to the identification and treatment of this emerging pathogen. Mycobacterium gordonae strain we isolated was resistant to trimethoprim-sulfamethoxazole but sensitive to ciprofloxacin, and long term administration (six months) induced complete healing of the cutaneous abscesses. CONCLUSION: Advanced laboratory diagnostic techniques have improved the isolation and identification of nontuberculous mycobacteria. The diagnosis requires a high index of clinical suspicion, as detection by conventional methods is difficult. To our knowledge, this patient is the first documented case of cutaneous infection from this pathogen in Italy.